Carpal Tunnel Syndrome: Associated Co-Morbidities in Saudi Arabia - Lutf A. Abumunaser (Journal of King Abdulaziz University: Medical Sciences, 2023)
The development of carpal tunnel syndrome appears to be associated with variety of factors. The aim of this article is to assess the frequency of comorbiditis (diabetes mellitus, hypothyroid, hypertension, and obesity) in patients with carpal tunnel syndrome in Saudi Arabia. 93 patients were included in this retrospective study. They were following in the orthopedic clinic of King Abdulaziz University Hospital, Jeddah, KSA from January 1999 to December 2009. Clinical data, laboratory, radiological and electrophysiological studies were collected from the medical records manually and electronically. 79 (86%) were female and 12 (13.2%) were male. The average age is 47 years (17-77) of all patients (male and female). Out of the 93 patients 30 (27%) had diabetes mellitus, 13 (15%) all female had hypothyroid, and 24 (26%) with hypertension. 29 (31%) were with body mass index range of 25-30, 28 (30%) with body mass index of 30-30, while 18 (19.3%) with body mass index of 35-40 and 16 (17.2%) were with body mass index of more than 40. Our study showed that diabetes mellitus, hypertension, hypothyroidism, and obesity are common associated comorbiditis of carpal tunnel syndrome in Saudi Arabia.